SUICIDE IN CONTEMPORANEITY: COULD PUBLIC POLICIES REDUCE THE SUICIDE RATES IN BRAZIL? - Sturza, Janaína Machado; Tonel, Rodrigo (Revista Direitos Humanos Fundamentais, 2019)
This research seeks to make a theoretical approach regarding the phenomenon of suicide and the increase of its occurrence in Brazil. Notwithstanding, the problem is based on the following questions: Why are suicides rates growing in the world? What political and legal measures should be proposed in a try to prevent the occurrence of this phenomenon? Are public policies the most effective means of reducing suicides? Thus, the goal of this investigation is to analyze the multicausal and multifactorial aspects of the suicide phenomenon.